The effectiveness of avalanche airbags - Haegeli, Pascal; Falk, Markus; Procter, Emily; Zweifel, Benjamin; Jarry, Frédéric; Logan, Spencer; Kronholm, Kalle; Biskupič, Marek; Brugger, Hermann (Resuscitation, 2014)
AIM: Asphyxia is the primary cause of death among avalanche victims. Avalanche airbags can lower mortality by directly reducing grade of burial, the single most important factor for survival. This study aims to provide an updated perspective on the effectiveness of this safety device. METHODS: A retrospective analysis of avalanche accidents involving at least one airbag user between 1994 and 2012 in Austria, Canada, France, Norway, Slovakia, Switzerland and the United States. A multivariate analysis was used to calculate adjusted absolute risk reduction and estimate the effectiveness of airbags on grade of burial and mortality. A univariate analysis was used to examine causes of non-deployment. RESULTS: Binomial linear regression models showed main effects for airbag use, avalanche size and injuries on critical burial, and for grade of burial, injuries and avalanche size on mortality. The adjusted risk of critical burial is 47% with non-inflated airbags and 20% with inflated airbags. The adjusted mortality is 44% for critically buried victims and 3% for non-critically buried victims. The adjusted absolute mortality reduction for inflated airbags is -11 percentage points (22% to 11%; 95% confidence interval: -4 to -18 percentage points) and adjusted risk ratio is 0.51 (95% confidence interval: 0.29 to 0.72). Overall non-inflation rate is 20%, 60% of which is attributed to deployment failure by the user. CONCLUSION: Although the impact on survival is smaller than previously reported, these results confirm the effectiveness of airbags. Non-deployment remains the most considerable limitation to effectiveness. Development of standardized data collection protocols is encouraged to facilitate further research.
Keywords: Multivariate Analysis; lidé; Asphyxia; asfyxie; airbagy; laviny; Avalanches; retrospektivní studie; Humans; multivariační analýza; Air Bags; Retrospective Studies